(untitled) (International Journal of Studies in Nursing, 2019)
Background: Recommendations to prevent pressure injuries (PI) consistently emphasize patients’ participation in care, without which interventions are less likely to be effective. Aim: To examine patients and/or their caregivers’ knowledge of risk factors and participation in PI preventive interventions. Subjects and Methods: This descriptive study was conducted among 70 patients in neurological and orthopaedic wards in the University College Hospital in Nigeria. The patients were purposively selected. Knowledge about risk factors for PI, level of participation in care and perceived barriers were examined using structured questionnaire. Findings: Mean age was age 49± 18years; 37(66.1%) did not consider they were at risk for PI. Poor knowledge of risk factors: incontinence (59.3%), dragging self out of bed (56.5%), loss of sensation (58.3), when the nurse drags than lifts (66.7%) was found. Mean knowledge of risk factors was 1.42±0.49 and level of participation (1.31± 0.47). Barriers to participation included inadequate instruction from nurses about what they or their caregivers needed to do (2.41±1.16); pain during repositioning (3.58±1.16); feeling incompetent to turn (3.10±1.27; caregivers not allowed to stay on the ward (3.47±1.12). Only education was significantly associated with level of participation (P= 0.002< 0.05). However, no significant association existed between the medical diagnosis of the patients and their level of participation (P = 0.347 >0.05). Conclusion: Patients’ knowledge of risk factors was poor and participation was also low. Well defined instructions should be provided during hospitalization to improve patient’s participation in care.